Impoliteness Strategies Found On Jennie’s Instagram - Ni Luh Putu Sri Widiastuti; I Nyoman Muliana; Dewa Ayu Kadek Claria (CV. Tirta Pustaka Press, 2024)
This research aims to analyze impoliteness strategies found in the Instagram comments of Jennie, a famous celebrity. The study employs a discourse analysis approach to identify and categorize various impoliteness strategies that may appear in these comments. Research data were collected from comments posted on Jennie's Instagram posts within a specific time frame. The results of the study reveal several impoliteness strategies commonly found in these comments, such as insults, mockery, and the use of offensive language. Additionally, the research identifies the contexts or situations that may trigger the use of these impoliteness strategies. Data analysis is conducted qualitatively, citing examples of comments that illustrate each impoliteness strategy. The findings of this research can provide insights into how celebrities like Jennie can become targets of impoliteness on social media and may assist in the development of strategies for handling and managing impolite comments on social media platforms. The study also offers a deeper understanding of social media users' behavior when interacting with public figures and the cultural and social implications of impoliteness strategies in online communication.